1999
DOI: 10.1086/314778
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy against Respiratory Syncytial Virus following Murine Neonatal Immunization with BBG2Na Vaccine: Influence of Adjuvants and Maternal Antibodies

Abstract: Alum-adsorbed BBG2Na, a recombinant vaccine derived in part from the respiratory syncytial virus (RSV) subgroup A G protein, induced moderate antibody titers after 1 immunization in 1-week-old mice but conferred complete lung protection upon RSV challenge. The anti-BBG2Na IgG1-IgG2a neonatal isotype profile was suggestive of dominant Th2 responses compared with those in adults. Formulation of BBG2Na with a Th1-driving adjuvant efficiently shifted neonatal responses toward a more balanced and adultlike IgG1-IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 41 publications
1
35
0
3
Order By: Relevance
“…In addition, the ability of RSV to evade immune responses in humans should continue to be investigated. We are suggesting that particular attention should be given to the development of candidate HRSV subunit vaccines including only the central region of the G protein (62). Considering the mutations in this region described here, this subunit-vaccine approach should be used with caution.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the ability of RSV to evade immune responses in humans should continue to be investigated. We are suggesting that particular attention should be given to the development of candidate HRSV subunit vaccines including only the central region of the G protein (62). Considering the mutations in this region described here, this subunit-vaccine approach should be used with caution.…”
Section: Discussionmentioning
confidence: 97%
“…However, it has been demonstrated that significant IgG responses may be induced after immunization with protein antigens (reviewed in [23]), indicating that T cell help to promote isotype switch of B cells from IgM to IgG is present already in the neonatal period of life. The IgG subclass pattern observed after early life immunization of mice is, nevertheless, characterized by a relatively high IgG1/IgG2a ratio [29,30]. This pattern reflects the Th2-biased conditions of the immune system in the newborn, shown by low production of IFN-c, but relatively high production of IL-4, IL-5 and IL-13 after immunization with TD antigens under neutral conditions [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the development of RSV vaccines has long been a priority for infants and young children (2, 6 -9), and more recently, vaccines are being developed for older children at risk for serious complications of infection and for the elderly (10 -12). RSV vaccine development has been focused toward live temperature-sensitive, attenuated vaccines and subunit vaccines based on the F and/or G glycoproteins (13,14). In animal model systems the F glycoprotein is the most effective, and G glycoprotein is the next most effective in inducing neutralizing Abs and protective immunity, but vaccination with the G glycoprotein generally induces only limited protection (15,16).…”
mentioning
confidence: 99%